ANALISIS KEPUASAN NASABAH DENGAN METODA SER VQUAL GUNA MENINGKATKAN KUALITAS PELAYANAN PERBANKAN DI PT BANK XYZ Tbk. KANTOR CABANG KEDIRI - Andjik Setyo Widodo; Bobby Oedy P. Soepangkat; Sony Sunaryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
Globalization and technological advancement and the resulting high market competitiveness is giving prominence to the issue of the quality of customer service in the service industry sector, leaving practitioners in the sector with no choice but to properly address the issue in order to be competitive. Consequently, assessing customer service quality in the financial service industry such as bank is vital in determining the standard expected of the industry. PT Bank XYZ (Persero) Tbk companie is no exception to this requirement. The purpose of this paper is to examine the level of service quality and customer satisfaction in bank.. The results of this investigation revealed that the service quality of PT Bank XYZ (Persero) Tbk branch of Kediri were unsatisfactory. The results also indicated that customers of bank companies rated. In terms of customer satisfaction, the result revealed that customers of PT Bank XYZ (Persero) Tbk branch of Kediri were not satisfied with the service of these banks. Implications and suggestions for further research are proposed.